2016
DOI: 10.1039/c5sc03350k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and mechanistic study of a photocatalytic indoline dehydrogenation for the synthesis of elbasvir

Abstract: Elbasvir is a potent NS5A antagonist for the treatment of chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 83 publications
5
113
0
1
Order By: Relevance
“…9294 This method appears to be the most promising avenue for conducting visible-light reactions at a preparative scale on complex substrates, as shown by a series of pioneering examples by Merck, most notably for the synthesis of elbasvir. 95 Following this general template, we constructed our reactor within the design principles of low cost, easy construction from commercially available parts, and that it should fit within a standard walk-in fume hood. 96 The reactor consisted of blue LED lights contained within a glass beaker wrapped with a single layer of perfluoroalkoxy (PFA) tubing (1.6 mm inner diameter) around the outside, giving a volume of approximately 150 mL (Figure 3A, see also Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…9294 This method appears to be the most promising avenue for conducting visible-light reactions at a preparative scale on complex substrates, as shown by a series of pioneering examples by Merck, most notably for the synthesis of elbasvir. 95 Following this general template, we constructed our reactor within the design principles of low cost, easy construction from commercially available parts, and that it should fit within a standard walk-in fume hood. 96 The reactor consisted of blue LED lights contained within a glass beaker wrapped with a single layer of perfluoroalkoxy (PFA) tubing (1.6 mm inner diameter) around the outside, giving a volume of approximately 150 mL (Figure 3A, see also Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was also scaled up to 100 g scale in batch and, although the reaction took 62 h, a 35% yield of the desired product was still obtained (vs 57% yield on 18 g scale). More recently, the Knowles group has collaborated with scientists at Merck to develop a photocatalytic dehydrogenation protocol for the synthesis of elbasvir, a NS5A antagonist for the treatment of hepatitis C. 170 Through these studies, a photoredox-mediated method was developed which enabled a high yield of indole 93 to be obtained with no erosion in the enantiopurity of the product (Scheme 36b). Mechanistic studies indicated that this reaction proceeds via a radical chain mechanism.…”
Section: Applications Of Photoredox Catalysismentioning
confidence: 99%
“…13,14 Reactors of this type have been applied across academia and industry with excellent success for gram-scale reactions. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, extension of these plug flow reactors to kilogram-scale production remains a significant challenge. One approach that has been pursued involves increasing the number of identical reactors operating in parallel, thereby increasing the overall throughput.…”
mentioning
confidence: 99%